2018
DOI: 10.1007/s40333-018-0095-x
|View full text |Cite
|
Sign up to set email alerts
|

Rainfall patterns of Algerian steppes and the impacts on natural vegetation in the 20th century

Abstract: Since 1960, the steppe regions of North Africa have been subject to an increasing desertification, including the degradation of traditional pastures. The initially dominant species (Artemisia herba-alba, Lygeum spartum and Stipa tenacissima) declined and were progressively replaced by other species (Atractylis serratuloides and Salsola vermiculata) that are more tolerant to the new conditions. It is not clear whether these changes are due to anthropogenic reasons or climatic determinism. We have carried out a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 13 publications
(16 reference statements)
1
6
0
Order By: Relevance
“…Because the source of water supply for this type of land use is the atmospheric precipitation, which has declined due to the occurrence of droughts. The same results have been reported by Hourizi et al, (2017) and Belala et al, (2018) [32][33]. Our results are also agree with the findings of Bouarfa et al, (2022) [34], who reported that the significant changes have occurred between the years 2002-2009 around the Djelfa, El Bayadh, and Ain Sefra regions (in the western part of our study area) due to the spatial-temporal extent of drought on steppe vegetation density and resilience.…”
Section: 6supporting
confidence: 91%
“…Because the source of water supply for this type of land use is the atmospheric precipitation, which has declined due to the occurrence of droughts. The same results have been reported by Hourizi et al, (2017) and Belala et al, (2018) [32][33]. Our results are also agree with the findings of Bouarfa et al, (2022) [34], who reported that the significant changes have occurred between the years 2002-2009 around the Djelfa, El Bayadh, and Ain Sefra regions (in the western part of our study area) due to the spatial-temporal extent of drought on steppe vegetation density and resilience.…”
Section: 6supporting
confidence: 91%
“…Desertification in arid or semi-arid areas has been an environmental issue in regions as geographically diverse as Northern China, the Sahel, or the southwestern United States. [1][2][3] Desertification is associated with anthropogenic causes, 4 such as overgrazing, [5][6][7] logging, or unsustainable agricultural practices, 2,8 and climate change, 9 specifically shifts in the spatial and temporal patterns of rainfall [10][11][12] and gale days (wind velocity greater than 17 m/s). 13,14 When combined, these effects can lead to rapid vegetation cover loss, and subsequent wind erosion can also cause large dust storms, 15 leading to increased fine particulate air pollution with associated adverse health impacts 16,17 and desert encroachment onto vegetated and inhabited areas.…”
Section: Introductionmentioning
confidence: 99%
“…Despite tree-planting efforts, desertification intensified on the steppes, especially in south-western Algeria, due to the prolonged drought during the 1980s. Rainfall declined in the range from 18% to 27%, and the dry season has increased by two months in the last century (Belala et al 2018). Livestock numbers in the Green Dam regions, mainly sheep, grew exponentially, leading to severe overgrazing, causing trampling and soil compaction, which greatly increased the risk of erosion.…”
Section: The Green Dam In Algeriamentioning
confidence: 99%